2016
DOI: 10.1016/j.matchemphys.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and thermal properties of biodegradable poly(hydroxybutyrate-co-hydroxyvalerate)/tungsten disulphide inorganic nanotube nanocomposites

Abstract: g r a p h i c a l a b s t r a c t a b s t r a c t Promising biodegradable and renewable poly(hydroxybutyrate co hydroxyvalerate) (PHBV) nano composites based on tungsten disulphide inorganic nanotubes (INT WS2) were efficiently prepared by a simple solution blending method The structure, morphology, thermal stability and crystallization behavior of the nanocomposites were investigated by ultra-high field emission scanning electron mi croscope (FESEM), thermogravimetric analysis (TGA), differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The value of initial degradation temperature (T i ) was equal to the temperature observed when the initial weight of the heated sample decreased by 2% (T 2 ) [28]. The study pertained also to another important thermal property, namely the correspondence between the applied temperature and the maximum rate of the weight loss (T p ), which is defined as the peak value of the first derivative (DTG) of the TGA curve (Fig.…”
Section: Tga Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…The value of initial degradation temperature (T i ) was equal to the temperature observed when the initial weight of the heated sample decreased by 2% (T 2 ) [28]. The study pertained also to another important thermal property, namely the correspondence between the applied temperature and the maximum rate of the weight loss (T p ), which is defined as the peak value of the first derivative (DTG) of the TGA curve (Fig.…”
Section: Tga Analysismentioning
confidence: 92%
“…where: ΔH m is melting enthalpy (J/g), ΔH cc is cold crystallization enthalpy (J/g), ΔH o m stands for the melting enthalpy of fully crystalline PHBV which equals to 146 J/g [26][27][28] and w(PHBV) is the weight fraction of PHBV in the sample.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The market for biodegradable and bio-based materials is becoming more and more popular, especially in applications where biodegradability provides an advantage for customers and environment. [1,2] Biodegradable polymers are increasingly used in all fields of medicine, for example, as dressings (mainly hydrogels), resorbable surgical threads, bone implants, and as drug delivery systems. [3] Biodegradable polymers are divided into two main groups: polyesters and polyglycols.…”
Section: Introductionmentioning
confidence: 99%
“…The use of plastics in everyday life has increased dramatically during the course of the 20th and 21st century which is primarily due to the characteristics that plastics offer in the development of new products to meet the challenges in modern society. Silverman et al [1] reported that in 2015, approximately 300 million tons of plastic material will be produced around the world, most of which will be derived from the ever depleting petroleum feedstocks and this has resulted in them attracting increasing interest owing to the growing concern with regards to both the environment and decrease in fossil resources [2].…”
Section: Introductionmentioning
confidence: 99%